2017
DOI: 10.1371/journal.pone.0180244
|View full text |Cite|
|
Sign up to set email alerts
|

Testosterone suppresses uropathogenic Escherichia coli invasion and colonization within prostate cells and inhibits inflammatory responses through JAK/STAT-1 signaling pathway

Abstract: Prostatitis is a common condition in adult men of all ages. Uropathogenic Escherichia coli (UPEC) are most frequent pathogen involved in bacterial prostatitis by refluxing the infected urine into prostatic ducts and resulting in an ascending urethral infection. However, the study about the mechanisms of UPEC to invade, replicate and persist in normal prostate epithelial cell is only few. Given the fact that UPEC is pathogen most frequently involved in prostatitis and that testosterone has been demonstrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…Ho and colleagues have shown that T not only inhibits the invasion and colonization of the uropathogenic Escherichia coli (UPEC), but has also reduced the levels of pro-inflammatory cytokines (IL-1β, IL-6, and IL- 8) induced by UPEC in a dose-dependent manner. In particular, T plays an anti-inflammatory role in LPS-induced prostate cell inflammation by down-regulating Janus kinases, signal transducer and activator of transcription proteins (JAK/STAT1) signaling pathway (JAK/STAT1) ( 27 ).…”
Section: Sex Hormones and Prostate In Agingmentioning
confidence: 99%
“…Ho and colleagues have shown that T not only inhibits the invasion and colonization of the uropathogenic Escherichia coli (UPEC), but has also reduced the levels of pro-inflammatory cytokines (IL-1β, IL-6, and IL- 8) induced by UPEC in a dose-dependent manner. In particular, T plays an anti-inflammatory role in LPS-induced prostate cell inflammation by down-regulating Janus kinases, signal transducer and activator of transcription proteins (JAK/STAT1) signaling pathway (JAK/STAT1) ( 27 ).…”
Section: Sex Hormones and Prostate In Agingmentioning
confidence: 99%
“…Moreover, in the case of hypogonadism, there is an increase in the level of systemically circulating proinflammatory cytokines (3). Suppression of systemic inflammatory responses was found when testosterone was administered externally to patients with hypogonadism (33,34).…”
Section: Testosterone and Hypogonadismmentioning
confidence: 99%
“…Dahası, hipogonadizm durumunda sistemik olarak dolaşan proenflamatuvar sitokinlerin düzeyinde artış meydana gelmektedir (3). Hipogonadizmi olan olgulara dışarıdan testosteron verildiğinde sistemik enflamatuvar cevaplarda baskılanma saptanmıştır (33,34).…”
Section: Testosteron Ve Hypogonadizmunclassified